The Role of Restitution in Trafficking - H Radea Respati Paramudhita (Jurnal Indonesia Sosial Teknologi, 2024)
Trafficking in Persons (TPPO) is a grave human rights violation because it causes various negative impacts on victims physically, psychologically, or socio-economically; one of the efforts to restore victims of TPPO is through restitution. This research explores the role of restitution in the context of TPPO. This research adopts a qualitative approach by collecting data through a literature study. Furthermore, the data is analysed through three stages: data reduction, data presentation, and conclusion drawing. The findings of the research indicate that restitution plays a vital role as a remedy and legal protection for victims of human trafficking. In its application, the punishment for the obligation to pay restitution can be replaced with imprisonment. Criminal punishment is not merely a deterrent effect on the convicted person, but recovery for the victim of the crime itself through restitution must be considered.